2015
DOI: 10.1002/ccd.25878
|View full text |Cite
|
Sign up to set email alerts
|

The new Occlutech® PDA occluder: Initial human experience

Abstract: Objectives: To evaluate the feasibility, safety, and efficacy of the Occlutech V R PDA occluder for closure of patent ductus arteriosus (PDA). Background: The Occlutech V R PDA occluder is novel, self-shaping Nitinol wire device with PET (polyethylene terephthalate) patches integrated into the shank of the device to assure a better obturation of the ductus. The Occlutech V R PDA occluder has undergone two design modifications. Methods: A prospective, non-randomized pilot study was started in November 2011. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 18 publications
2
34
0
Order By: Relevance
“…Kudumula et al reported that ductal occlusion did not occur immediately in patients who underwent transcatheter closure of PDA using the ODO . Also, Abdelbasit et al indicated 48.5% complete occlusion rate at 10 minutes post‐implant, they stated patients having large PDAs tend to have residual shunt but it achieves complete closure about 90 days . According to our data, complete occlusion at the end of procedure was achieved only in 63% of the patients supporting the results of Kudumula et al Despite the differences in early occlusion rates, final occlusion rates are similar with ADO‐I.…”
Section: Discussionsupporting
confidence: 85%
“…Kudumula et al reported that ductal occlusion did not occur immediately in patients who underwent transcatheter closure of PDA using the ODO . Also, Abdelbasit et al indicated 48.5% complete occlusion rate at 10 minutes post‐implant, they stated patients having large PDAs tend to have residual shunt but it achieves complete closure about 90 days . According to our data, complete occlusion at the end of procedure was achieved only in 63% of the patients supporting the results of Kudumula et al Despite the differences in early occlusion rates, final occlusion rates are similar with ADO‐I.…”
Section: Discussionsupporting
confidence: 85%
“…Reported case series in the literature confirm the high occlusive properties of the ODO, even though larger ducts usually require more time to close [8,9]. Our present results demonstrate a 100% success rate (shunt closure and successful implantation) with zero mortality and no serious morbidity.…”
Section: Safety and Efficacysupporting
confidence: 72%
“…A size difference of 1 mm resulted in an appropriate device stability in contrast to 3–4 mm oversizing that were necessary in their experience with previous devices . Boudjemline et al and Abdelbasit et al, who are also reporting their initial experience with the Occlutech ® PDA Occluder implanted the 8/10 mm device maximum as well . In our study with large PDA > 5 mm and additional PAH the maximum available device size was used (14/18) twice (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…The interventionalist's armamentarium nowadays consists of a wide range of various occluder types and coils, mostly nitinol‐based and self‐expanding . The closing procedure itself is considered a standard procedure in most pediatric cath labs with excellent results . However, closure of PDA with very large diameters (PDA/Ao ratio > 0.5) still remains a complex challenge, especially when an elevated pulmonary artery pressure is present .…”
Section: Introductionmentioning
confidence: 99%